Використання поліських лісових ландшафтів Рівненщини у рекреації та туризмі - Чабанчук, Валентина Юріївна; Мельнійчук, Михайло Михайлович; Chabanchuk, Valentyna Yu.; Melniichuk, Mykhailo M. (Тернопільський національний педагогічний університет імені Володимира Гнатюка, 2015)
У статті розглянута роль лісових ландшафтів Рівненщини у сфері рекреації. Досліджено осередки збереження природних лісових ландшафтів та показники лісистості по території області. Вивчено головні якісні характеристики рекреаційних лісів на території Рівненської області. Проведено аналіз форм організації рекреації в лісах Рівненщини. Охарактеризовано видовий склад і вікову структуру лісів як індикаторів лікувально-оздоровчих та санітарно-гігієнічних функцій лісу. Визначено ступінь фітонцидності переважаючих порід та показники естетичної цінності поліських лісів за методикою В. Мацоли. Проаналізовано основні заняття з рекреаційного використанням лісових ресурсів та проблеми, що гальмують розвиток рекреації та туризму.

In the article we analyzed the role of forest landscape of Rivne region in recreation, rehabilitation and treatment. We explored the main centers of conservation of natural forest landscapes. We have identified regions with the highest and lowest rates of forest cover, and on the basis of this study constructed a map of of forest cover by districts. Recreational forests were studied as a component of natural recreational resources. It was determined a total area of forests that can be used for recreational activities in the area. We conducted an analysis of forms of recreation in forests of Rivne region and recreational activities by functional features. The main quality characteristics of recreational forest in the territory of Rivne region were investigated. We described the species composition and age structure of forests as indicators of therapeutic and sanitary functions of forests. It was determined indicators aesthetic value of forest areas according to the method of B. Matsolya. We explored the main occupation of the recreational use of the forest resources in Polesie and the main problems that hinder the development of tourism and recreation in the forests.
Using of polissyan forest landscapes of Rivne region in recreation and tourism
Keywords: лісовий ландшафт; рекреаційна діяльність; рекреаційні ліси; лісистість; фітонцидність; естетична цінність; forest landscape; recreational activities; recreational forests; forest cover; aesthetic value; forest resources